PERAN GURU AQIDAH AKHLAK DALAM PEMBENTUKAN RELIGIOSITAS PERILAKU KESEHARIAN DI PONDOK PESANTREN DAAR EL-QOLAM - Didi Setiawan (QATHRUNÂ, 2021)
This study aims to 1) determine the reasons for the formation of religious students and daily behavior at MTs Daar El Qolam Gintung. 2) find out the daily behavior of students at MTs Daar El Qolam Gintung. 3) find out the efforts of the Aqidah Akhlak teacher in forming Religiosity and Daily Behavior at MTs Daar El Qolam Gintung. This type of research is descriptive with a qualitative approach. Meanwhile, the research sources are the leaders, Islamic boarding schools, the head of the care section, the head of the worship department, the principal, the teacher / teacher and the students. The data collection technique is done through interviews and observation and documentation. The data analysis technique was carried out using data collection, data reduction, data presentation and data conclusion. The findings in this study are the role of aqidah akhlak teacher in shaping the daily behavior of students at MTs Daar El Qolam 1 Gintung, 1) as a guide, aqidah akhlak teacher to motivate and give advice to students to always do good. 2) acting as an educator, namely teaching according to norms and rules. 3) as an evaluator, aqidah akhlak teacher always admonishes and gives advice to students who violate the rules, give sanctions to students who violate the rules. It is hoped that this research will be useful for the Daar el-Qolam Islamic boarding school in particular and also benefit other educational institutions so that it can be implemented properly and correctly.